TINJAUAN TEOLOGI SISTEMATIS-APOLOGETIS TERHADAP PANDANGAN ADOPSIONISME MENGENAI KETUHANAN YESUS - HENDRIK YUFENGKRI SANDA (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2020)
Jesus is a unique person because he has two natures, namely God and Human. The Bible explicitly teaches and testifies on this subject. But in fact, some views reject both His divine nature and even His humanity. These views have been around since Jesus' incarnation in the world until now. One of the teachings which classify as Christian heretics in the early centuries was the adoptionist view, which taught Jesus only human beings who adopt as children of God later. It means they reject the divinity and also the pre-existence of Christ as God before His incarnation. This study intends to criticize the adoptionist idea. The method used is qualitative research through a systematic-apologetic approach. The results showed that the view of adoption was wrong because it violated the principle of the divine nature of Jesus as the Bible teaches. Jesus is Lord from the beginning, not after His incarnation.